Issues of therapy for biliary pathology in children: the choice of the optimal solution - O.V. Shutova; N.V. Pavlenko; O.N. Babadganyan; I.G. Solodovnichenko; O.V. Buksha (Zaslavsky O.Yu., 2018)
Background. Diseases of the hepatobiliary system are one of the most important problems of pediatric gastroenterology. Lesions of the biliary tract are associated with persistent changes in lipid metabolism that contributes to the prolonged cholestasis and to the progression of the biliary pathology. The purpose of this study was to evaluate the efficacy and safety of Ursofalk® in the comprehensive therapy of biliary tract diseases and comorbid pathology in children. Materials and methods. The results of examination and integrated treatment of 55 children aged 5 to 18 years (31 girls and 24 boys) with diseases of the biliary tract and comorbid pathology were analyzed. The criteria for inclusion of patients in the study were: the presence of diseases of the biliary tract accompanied by biliary sludge and blood lipid disorders. Diagnostic complex included: analysis of clinical data, ultrasound examination of abdominal organs, biochemical blood analysis (liver tests, lipid disorders). Depending on the comorbid pathology, all children received comprehensive treatment within a month. Patients were divided into two groups depending on choleretic therapy: group 1 (main) received conventional cholagogues, group 2 (comparison) - Ursofalk®. Licensed software products (Statistica, Excel) were used for statistical processing of the obtained data. Results. By the end of the treatment with Ursofalk® we observed positive dynamics in patients' condition and laboratory indicators. In patients who received Ursofalk®, the manifestations of pain syndrome and dyspepsia completely disappeared. Children from the comparison group still had pain syndrome, a feeling of heaviness in the right upper quadrant and dyspepsia. The use of Ursofalk® normalized the parameters of the bile structure and the biochemical parameters of lipid metabolism. We registered a significant (p < 0.05) decrease in the incidence of impaired bile homogeneity - by 65.5 % in children from the main group. In children of the comparison group, it decreased only by 27.3 %. Positive dynamics of biochemical parameters was observed in both groups of patients, but with significant changes (p < 0.05) in the group of children taking Ursofalk®. Conclusions. Ursodeoxycholic acid (UDCA) use is pathogenetic justified for the correction of functional and metabolic disorders in biliary and comorbid pathologies in children. Ursofalk® administration in the comprehensive therapy of the diseases of the biliary system in children led to the rapid regression and relief of clinical symptoms and the improvement of laboratory-instrumental indicators. Ursofalk® is a reference product of UDCA. Availability of the officinal form of Ursofalk® in a special form for children (suspension) allows UDCA to be used in childhood, starting from the first days of life.